Influence of airborne transmission of SARS-CoV-2 on COVID-19 pandemic. A review - Domingo, José L. (Environ Res, 2020)
In recent years, a number of epidemiological studies have demonstrated that exposure to air pollution is associated with several adverse outcomes, such as acute lower respiratory infections, chronic obstructive pulmonary disease, asthma, cardiovascular diseases, and lung cancer among other serious diseases. Air pollutants such as sulfur oxides, nitrogen oxides, carbon monoxide and dioxide, particulate matter (PM), ozone and volatile organic compounds (VOCs) are commonly found at high levels in big cities and/or in the vicinity of different chemical industries. An association between air concentrations of these pollutants and human respiratory viruses interacting to adversely affect the respiratory system has been also reported. The present review was aimed at assessing the potential relationship between the concentrations of air pollutants on the airborne transmission of SARS-CoV-2 and the severity of COVID-19 in patients infected by this coronavirus. The results of most studies here reviewed suggest that chronic exposure to certain air pollutants leads to more severe and lethal forms of COVID-19 and delays/complicates the recovery of patients of this disease.